Clinical practice guidelines for the prevention and treatment of osteoporosis in Taiwan: 2022 update - Ta-Wei Tai; Chun-Feng Huang; Huei-Kai Huang; Rong-Sen Yang; Jung-Fu Chen; Tien-Tsai Cheng; Fang-Ping Chen; Chung-Hwan Chen; Yin-Fan Chang; Wei-Chieh Hung; Der-Sheng Han; Ding-Cheng Chan; et al. (Journal of the Formosan Medical Association, 2023)
Osteoporosis greatly increases the risk of fractures. Osteoporotic fractures negatively impact quality of life, increase the burden of care, and increase mortality. Taiwan is an area with a high prevalence of osteoporosis. This updated summary of guidelines has been developed by experts of the Taiwan Osteoporosis Association with the intention of reducing the risks of osteoporotic fractures and improving the quality of care for patients with osteoporosis. The updated guidelines compile the latest evidence to provide clinicians and other healthcare professionals with practical recommendations for the prevention, diagnosis, and management of osteoporosis under clinical settings in Taiwan.